2015
DOI: 10.1002/adv.21632
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Core–Shell Ratio of Acrylic Impact Modifier on Toughening PLA

Abstract: Acrylic impact modifier (ACR), one kind of methyl methacrylate–butyl acrylate copolymer with a core–shell structure, was prepared by seed emulsion polymerization. The weight ratio of core–shell ranges from 85.5/14.5 to 71.9/28.1. Then PLA/ACR blends were prepared with a constant ratio of 80/20. The effect of core–shell ratio of ACR on toughening PLA was investigated. Torque analysis revealed that the torque values of PLA/ACR blends increased with increasing shell content of ACR. The impact strength of PLA/ACR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…5(a-f), the impact fracture surface of pure PLA showed relatively smooth, indicating that little shear yielding had taken place during the impact test. This was in agreement with low impact strength of pure PLA 31. FromFig.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…5(a-f), the impact fracture surface of pure PLA showed relatively smooth, indicating that little shear yielding had taken place during the impact test. This was in agreement with low impact strength of pure PLA 31. FromFig.…”
supporting
confidence: 89%
“…Core-shell impact modiers, such as acrylic impact modier (ACR), 27,28 acrylonitrile-butadiene-styrene (ABS) 29 and methyl methacrylate-butadiene-styrene (MBS), 30 are important types of toughener of PLA. Li et al 31 have reported that ACR with different core-shell ratios were synthesized and used to toughen PLA. The impact strength of PLA could be signicantly improved by ACR.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, polymers functionalized with maleate (nonacrylate [13][14][15][16][17][18][19] ) and glycidyl methacrylate groups (acrylate [20][21][22][23][24][25][26][27][28][29][30] ) are often employed. Additives containing these functionalities can be perfectly combined with PLA, especially if they are constituted by a common skeleton and provide polymer blends with improved ductility and strength.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the toughness of PLA, some strategies such as plasticization [ 15 , 16 , 17 , 18 ], copolymerization [ 19 , 20 , 21 ] and blending with tough polymers and thermoplastic elastomers were widely adopted [ 22 , 23 , 24 , 25 ]. Core-shell structured elastomer particles are another important toughener of PLA [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. As we know, the typical core-shell particles include an elastic rubber core phase, such as polybutadiene and poly (butyl acrylate), and a hard plastic shell phase, such as polystyrene and poly (methyl methacrylate).…”
Section: Introductionmentioning
confidence: 99%